The association between Dietary Obesity-Prevention Score (DOS) and type 2 diabetes (T2D): a case-control study - El-Sehrawy, Amr Ali Mohamed Abdelgawwad; Alharbi, Saud Salman; Maashi, Marwah Suliman; Ahmad, Irfan; Menon, Soumya V.; Thakur, Vishal; Anand, D. Alex; Sahoo, Samir (Frontiers in Nutrition, 2025)
BackgroundThe global prevalence of type 2 diabetes (T2D) continues to rise, with dietary patterns recognized as a major contributing factor in its development. The Dietary Obesity-Prevention Score (DOS) is a validated tool designed to evaluate adherence to dietary behaviors associated with obesity prevention. This case-control study aimed to examine the association between adherence to the DOS and the risk of developing T2D.MethodsParticipants were recruited from individuals attending medical clinics affiliated with King Khalid University in Abha, Saudi Arabia. The study included adults aged 18–60 years, comprising 250 newly diagnosed T2D cases (diagnosed within the past 6 months) and 250 healthy controls. Dietary intake was carefully assessed using a validated semi-quantitative food frequency questionnaire (FFQ), which covered a comprehensive list of 152 food items. The DOS is a validated index derived from 14 food groups known to be associated with changes in body weight.ResultsParticipants diagnosed with T2D exhibited significantly higher mean body weight (71. vs. 65.3 kg) and BMI (29.4 vs. 26.2 kg/m2) compared to the control group (p < 0.05). Participants in the highest tertile of the DOS exhibited significantly greater intakes of energy, carbohydrates, various micronutrients, fruits, vegetables, whole grains, and legumes, alongside lower consumption of saturated fatty acids, refined grains, and sugar-sweetened beverages (p < 0.05). No statistically significant differences were observed for these dietary components between the case and control groups. Higher adherence to the DOS was linked to a reduced risk of type 2 diabetes. After adjusting for potential confounders-including age, sex, energy intake, education, marital status, waist circumference, Waist-to-height ratio (WHtR), physical activity, and BMI-those in the highest DOS tertile demonstrated a 42% reduction in the odds of developing T2D compared to individuals in the lowest tertile (OR = 0.58; 95% CI: 0.38–0.87; P-trend = 0.038).DiscussionHigher adherence to DOS score associated with a lower risk of T2D among Saudi adults. To validate these findings and clarify the underlying causal mechanisms, further longitudinal studies and randomized controlled trials are warranted.